The Sacred of Religion and the Sublime of Ideology: Constructing Collective Identity through ReligiousSolidarities - De Guzman, Emanuel (Social Sciences and Development Review, 2016)
The sacred is ontologically central to the discursive construction of collective identity. Being the institutional expression of the sacred, religion is a staple in all human collectivities and a constitutive force in forging group identities. Hence, religion is coeval and coterminous with society and the human being: religion is society’s birthright and fate. As an ontologically religious being who derives an identity from the social body, the human being is always susceptible to ideological corruption, to an excessive forging of identity and solidarity that blurs the sense of the other, that which is fundamental in the human as a social being. The observed fatal journey of group solidarities from the sacred to religion to ideology in history provides a wealth of data for theorizing the process of ideologization and the susceptibility of religion to undergo this process. The answer lies in the the structure sacred-religion ideology where ideology is seen as an embedded corruptive symptom in all social groups.
Keywords: ideological corruption; collective representation; collective identity; sacred; religious solidarity; resurgence of religion